Basic and Clinical Aspects of Non-neuronal Acetylcholine: Biological and Clinical Significance of Non-canonical Ligands of Epithelial Nicotinic Acetylcholine Receptors - Sergei A. Grando (Elsevier, 2008)
Mucocutaneous keratinocytes and bronchial epithelial cells express nicotinic acetylcholine receptors (nAChRs). Emerging evidence indicates that nAChRs can be stimulated also by the tobacco-derived nitrosamines 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanone (NNK) and N '-nitrosonornicotine (NNN) that can induce tumors in laboratory animals. Nitrosamines may disturb the delicate balance between cell proliferation, growth arrest, and apoptosis. A novel paradigm of cell regulation via nAChR has been discovered in studies of SLURP (secreted mammalian Ly-6/urokinase plasminogen activator receptor-related protein)-1 and -2. Experimental results suggest that SLURP-1 and -2 regulate keratinocyte proliferation, apoptosis, and differentiation. Most importantly, SLURPs and professional nicotinic antagonists can abolish, in part, the abilities of NNK and NNN to cause tumorigenic transformation of immortalized keratinocytes. Learning the pharmacology of the nitrosamine vs. SLURP action on epithelial cells may help develop an effective anti-cancer treatment and prevention programs wherein hazardous effects of tobacco products are anticipated, or even abolished, by a pharmacologic ligand of the specific nicotinic receptor acting as an antidote. Keywords:: keratinocyte, nicotinic acetylcholine receptor, SLURP-1, SLURP-2, nitrosoamine, non-neuronal cholinergic system